Instantaneous biosynthesis of silver nanoparticles by selected macro fungi - Chan, Stephanie; Mashitah, M. (INSInet Publications, 2012)
Silver nanoparticles (AgNPs) have been reported to be useful in various medical and life sciences related application. It has received considerable attention in order to develop an efficient methodology for its synthesis. Conventional chemical synthesis is said to be harmful when used in medical related applications. Hence, this study was carried out with locally isolated fungi to synthesize silver nanoparticles biologically. Three modes of biosynthesis were identified: biosynthesis with the mycelia for extracellular and intracellular cells synthesis and sans mycelia for culture free synthesis. The white rot fungus, Schizophyllum commune, was found to have an ability to produce AgNPs instantaneously. The biosynthesis of AgNPs was further confirmed with gas chromatography-mass spectroscopy (GC-MS), UV-visible spectroscopy, and Zetasizer Nano ZS.